Effects of egg size on hatchability parameters and chick quality in native chicken: Egg size on hatchability - Rajesh Kumar,; Kirti Jamwal,; Nitin Bhardwaj,; Varun Sankhyan,; Krishanender Dinesh,; Shivani Katoch, (Indian Journal of Poultry Science, 2025)
Fertility and hatchability are traits of major economic importance in poultry industry as they have strong effect on overall chick output. Several factors have been proven to have an effect on the hatchability parameters of poultry eggs. Egg size is one of the crucial factors that may influence hatchability and success of chick output. The aim of present study was to investigate the effects of egg size on different hatchability parameters and chick quality in native chicken. Nine hundred nine eggs were weighed, labeled, and sorted equally into three groups: small, medium, and large as per Indian standards for table eggs. Eggs were evaluated for weight loss during incubation, fertility, embryonic mortality, hatchability, weight of hatched chick and chick yield. Egg size had a significant effect on fertility and hatchability traits. On total eggs set basis, the medium egg size group had the highest percentages of hatchability and fertility, followed by the small and large egg size groups. However, for fertile eggs set basis, the medium egg size group had the highest percentages of hatchability and fertility, followed by the small and large egg size groups. Large size egg group had significantly (P≤0.05) higher embryonic mortality during first and third week of incubation compared to small and medium size eggs. Similar trend was observed for percent infertile eggs. On pipped-not-hatched eggs, the impact of egg size was not statistically significant. Maximum numbers of chicks were culled in the large size egg group. Chick weight and chick length were significantly (P≤0.05) affected by egg size, and this effect increased as egg size increased. However, egg size had no significant effect on chick yield. Thus, it can be concluded that medium and small-sized eggs are more suitable than large-sized eggs for enhancing the efficiency of chick production, particularly in terms of the number of salable day-old chicks.